Calculation of electromagnetic wave scattering by a small impedance particle of an arbitrary shape - Ramm, Alexander G.; Andriychuk, M. I. (My University, 2014)
Scattering of electromagnetic (EM) waves by small (ka ≪ 1) impedance particle D of an arbitrary shape, embedded in a homogeneous medium, is studied. Analytic, closed form, formula for the scattered field is derived. The scattered field is of the order O(a[superscript 2 − κ]), where κ ∈ [ 0,1) is a number. This field is much larger than in the case of Rayleigh-type scattering. The numerical results demonstrate a wide range of applicability of the analytic formula for the scattered field. Comparison with Mie-type solution is carried out for various boundary impedances and radii of the particle.
Keywords: Electromagnetic waves; Wave scattering by small body; Boundary impedance; Computational testing